2017
DOI: 10.1021/acs.est.7b00807
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Antimony Adsorption on {001} TiO2: XAFS and DFT Study

Abstract: Antimony (Sb) contamination poses an emerging environmental risk, whereas its removal remains a contemporary challenge due to the lack of knowledge in its surface chemistry and efficient adsorbent. In this study, self-assembly {001} TiO was examined for its effectiveness in Sb removal, and the molecular level surface chemistry was studied with X-ray absorption spectroscopy and density functional theory calculations. The kinetics results show that Sb adsorption followed the pseudo-second order reaction, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 46 publications
7
49
0
Order By: Relevance
“…Nano‐ or microcrystals with exposed high‐index facets are of paramount significance to both fundamental research and technical applications by virtue of their copious atomic steps, kinks, ledges, dangling bonds, and abundant unsaturated coordination sites , , . For instance, we observed that high‐index {201} TiO 2 exhibited better adsorption and photooxidation performance than that of three low‐index {001}, {100}, and {101} TiO 2 materials . This observation is ascribed to the surface energy, which follows the order {201} (1.72 J/m 2 ) > {001} (0.90 J/m 2 ) > {010} (0.53 J/m 2 ) > {101} (0.44 J/m 2 ) , .…”
Section: Fundamental Backgroundmentioning
confidence: 83%
See 2 more Smart Citations
“…Nano‐ or microcrystals with exposed high‐index facets are of paramount significance to both fundamental research and technical applications by virtue of their copious atomic steps, kinks, ledges, dangling bonds, and abundant unsaturated coordination sites , , . For instance, we observed that high‐index {201} TiO 2 exhibited better adsorption and photooxidation performance than that of three low‐index {001}, {100}, and {101} TiO 2 materials . This observation is ascribed to the surface energy, which follows the order {201} (1.72 J/m 2 ) > {001} (0.90 J/m 2 ) > {010} (0.53 J/m 2 ) > {101} (0.44 J/m 2 ) , .…”
Section: Fundamental Backgroundmentioning
confidence: 83%
“…For instance, we observed that high‐index {201} TiO 2 exhibited better adsorption and photooxidation performance than that of three low‐index {001}, {100}, and {101} TiO 2 materials . This observation is ascribed to the surface energy, which follows the order {201} (1.72 J/m 2 ) > {001} (0.90 J/m 2 ) > {010} (0.53 J/m 2 ) > {101} (0.44 J/m 2 ) , . {201} facets have more uncoordinated Ti atoms, facilitating the photogeneration of hydroxyl radicals.…”
Section: Fundamental Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…This is because the Sb(III) species (i.e., Sb(OH) 3 ) in the aqueous solution remain unchanged from pH 3 to 10. 27…”
Section: Sb(iii) Sorption Kineticsmentioning
confidence: 99%
“…The adsorption capacity of these materials tends to be poor. Only a few sorbents such as metal-loaded Zr(IV), Fe(III) saponified orange waste 13 , zero-valent iron nanoparticles coatings on aluminum and silicon minerals 14,15 , iron oxyhydroxides 5 , zirconium oxide (Zr-O)-carbon nanofibers 7 , reduced graphene oxide/Mn3O4 16 , MnO2 nanofibers 17 , TiO2 18 , and UiO-66NH2 19 have reported promising results for both Sb(III) and Sb(V) adsorption. However, readily available and cost-effective materials are required to remediate Sb from contaminated water.…”
Section: Introductionmentioning
confidence: 99%